2019
DOI: 10.3390/molecules25010049
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Preparation of Synergistic Nanoantimicrobials

Abstract: The rapid spreading of resistance among common bacterial pathogens towards the misused antibiotics/disinfectant agents has drawn much attention worldwide to bacterial infections. In light of this, the present work aimed at the realization of core-shell nanoparticles possessing remarkable antimicrobial properties thanks to the synergistic action of the metal core and the disinfectant shell. Copper nanoparticles stabilized by benzalkonium chloride were prepared, characterized, and implemented in poly-vinyl-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…The embedding of metal nanoparticles (copper ones, in principle) in polymer matrices could help in the tuning of metal release properties, and at the same time in minimizing the risk of nanoparticle release into the environment [53]. Moreover, very simple and reliable routes to synergistic nanoparticles combining a copper core and a quaternary ammonium shell (both of which are capable, in principle, of expressing a strong antiviral action) are available in recent literature [63].…”
Section: Antiviral Drug Virus Infection Action Mechanism Referencesmentioning
confidence: 99%
“…The embedding of metal nanoparticles (copper ones, in principle) in polymer matrices could help in the tuning of metal release properties, and at the same time in minimizing the risk of nanoparticle release into the environment [53]. Moreover, very simple and reliable routes to synergistic nanoparticles combining a copper core and a quaternary ammonium shell (both of which are capable, in principle, of expressing a strong antiviral action) are available in recent literature [63].…”
Section: Antiviral Drug Virus Infection Action Mechanism Referencesmentioning
confidence: 99%
“…The study revealed that metal-loaded nanocomposites or metal embedded copper nanoparticles in polymer matrices are very effective against viral pathogens. Moreover, the combination of copper nanoparticles with quaternary ammonium shell exhibits potential antiviral activity [57].…”
Section: Nanoparticles-based Antiviral Coatingsmentioning
confidence: 99%
“…When the asymmetric salt BDHAC was used as a stabilizer, the electrochemical parameters did not lead to the same optimal results, and fast precipitation and NP aggregation were observed. Therefore, an increased surfactant concentration was used with the aim of inducing a greater stabilizing effect and balancing the smaller steric hindrance of BDHAC as a shell-forming component [44]. Moreover, THF was tested as a single solvent to prevent phase separation during CuNP inclusion in the NVs.…”
Section: Synthesis and Morphological Characterization Of Cunpsmentioning
confidence: 99%
“…Therefore, an increased surfactant concentration was used with the aim of inducing a greater stabilizing effect and balancing the smaller steric hindrance of BDHAC as a shell-forming component [44]. Moreover, THF was tested as a single solvent to prevent phase separation during CuNP inclusion in the NVs.…”
Section: Synthesis and Morphological Characterization Of Cunpsmentioning
confidence: 99%
See 1 more Smart Citation